Battery separator and battery

CN122935832APending Publication Date: 2026-10-16LG CHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580019558.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-12-17
Filing Date
2025-12-17
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

[0045]本发明的电池分隔件的一个表面可以缓冲外部物理刺激,以及另一个表面可以增加离子传导性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The battery separator and the battery of the present invention include: a base layer; a first electrolyte layer disposed on one surface of the base layer and containing a first electrolyte composition; a second electrolyte layer disposed on the other surface of the base layer and containing a second electrolyte composition; and inorganic particles, wherein the solid content (wt%) of the first electrolyte composition can be greater than the solid content (wt%) of the second electrolyte composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This document claims the benefit of Korean Patent Application No. 10-2024-0188592, filed with the Korean Intellectual Property Office on December 17, 2024, the entire contents of which are incorporated herein by reference.

[0002] This invention relates to a battery separator.

[0003] This invention relates to a battery. Background Technology

[0004] Gel polymer electrolytes (GPEs) can contain both a binder and a liquid electrolyte. GPEs are typically incorporated into the electrodes of a battery and can be bonded to the electrode active materials. In this case, a polyolefin-based membrane can be placed between the electrodes (positive and negative) to act as a separator to prevent physical short circuits between the electrodes.

[0005] A lithium metal battery is a battery that uses lithium metal as the negative electrode active material. Summary of the Invention

[0006] Technical issues

[0007] The negative electrode of a lithium metal battery may expand during charging and discharging. An expanded negative electrode can cause cracks in the positive electrode. Cracks in the positive electrode can adversely affect battery performance. Excellent battery performance can only be ensured when the expansion of the negative electrode is suppressed, or when even if the negative electrode expands, it will not cause cracks in the positive electrode.

[0008] Technical solution

[0009] One embodiment of the present invention is a battery separator, comprising: a base layer; a first electrolyte layer disposed on one surface of the base layer and comprising a first electrolyte composition; a second electrolyte layer disposed on another surface of the base layer and comprising a second electrolyte composition; and inorganic particles, wherein the solid content (wt%) of the first electrolyte composition is greater than the solid content (wt%) of the second electrolyte composition.

[0010] The ratio (SC1 / SC2) of the solid content (SC1, wt%) of the first electrolyte composition to the solid content (SC2, wt%) of the second electrolyte composition can be 1.05 or greater.

[0011] The first electrolyte composition comprises a first binder, a first liquid electrolyte, and a first crosslinking agent, and the second electrolyte composition comprises a second binder, a second liquid electrolyte, and a second crosslinking agent, wherein the content (by weight) of the first liquid electrolyte in the first electrolyte composition may be less than the content (by weight) of the second liquid electrolyte in the second electrolyte composition.

[0012] The first and second binders may each independently comprise a first unit of vinylidene fluoride and a second unit of a fluorinated alkyl vinyl compound.

[0013] The weight-average molecular weight (g / mol) of the first binder and the second binder can each independently range from 150,000 to 600,000, and the content (wt%) of the second unit of the first binder and the second binder can each independently range from 10 to 25.

[0014] The first liquid electrolyte and the second liquid electrolyte may each independently contain a non-aqueous solvent, a lithium salt, and additives.

[0015] The first crosslinking agent includes a first-1 crosslinking agent and a first-2 crosslinking agent, and the second crosslinking agent includes a second-1 crosslinking agent and a second-2 crosslinking agent. The number of crosslinkable functional groups in the first-1 crosslinking agent may be greater than the number of crosslinkable functional groups in the first-2 crosslinking agent, and the number of crosslinkable functional groups in the second-1 crosslinking agent may be greater than the number of crosslinkable functional groups in the second-2 crosslinking agent.

[0016] The first-1 crosslinking agent and the second-1 crosslinking agent can each independently comprise monomeric compounds.

[0017] The number of crosslinkable functional groups in the first-1 crosslinking agent and the number of crosslinkable functional groups in the second-1 crosslinking agent can each be 3 or more independently.

[0018] The first-1 crosslinking agent and the second-1 crosslinking agent may each independently include compounds based on tri(meth)acrylate, compounds based on tetra(meth)acrylate, compounds based on penta(meth)acrylate, compounds based on hexa(meth)acrylate, or combinations thereof.

[0019] The first-1 crosslinking agent and the second-1 crosslinking agent may each independently include trimethylolpropane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, glycerol tri(meth)acrylate, ethoxylated glycerol tri(meth)acrylate, propoxylated glycerol tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and pentaerythritol tetra(methyl) Acrylates, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, erythritol tetra(meth)acrylate, bis(trimethylolpropane) tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ethoxylated dipentaerythritol penta(meth)acrylate, sorbitol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, sorbitol hexa(meth)acrylate, or combinations thereof.

[0020] The first and second crosslinking agents can each independently comprise polymer compounds.

[0021] The number of crosslinkable functional groups in the first-2 crosslinking agent and the number of crosslinkable functional groups in the second-2 crosslinking agent can both be 2.

[0022] The first-2 crosslinking agent and the second-2 crosslinking agent may each independently comprise a compound based on di(meth)acrylate.

[0023] The first-2 crosslinking agent and the second-2 crosslinking agent may each independently include polyethylene glycol di(meth)acrylate, poly(ethylene oxide-propylene oxide) di(meth)acrylate, polyurethane di(meth)acrylate, polycarbonate di(meth)acrylate, or combinations thereof.

[0024] The weight ratio (C1-1:C1-2) of the first-1 crosslinking agent of the first electrolyte layer to the weight (C1-2) of the first-2 crosslinking agent of the first electrolyte layer, and the weight ratio (C2-1:C2-2) of the second-1 crosslinking agent of the second electrolyte layer to the weight (C2-2) of the second-2 crosslinking agent of the second electrolyte layer, can each be independently within the range of 1:9 to 9:1.

[0025] The first electrolyte layer and the second electrolyte layer can each independently contain linear carbonate-based compounds in a volume larger than that of cyclic carbonate-based compounds.

[0026] Compounds based on linear carbonates may include dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl ethyl carbonate, or combinations thereof.

[0027] Compounds based on linear carbonates can be liquids at room temperature.

[0028] Compounds based on cyclic carbonates may include ethylene carbonate, vinylene carbonate, ethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, propylene carbonate, butyl carbonate, or combinations thereof.

[0029] Compounds based on cyclic carbonates can be solid at room temperature.

[0030] The volume (volume %) of the linear carbonate-based compound in the first electrolyte layer and the volume (volume %) of the linear carbonate-based compound in the second electrolyte layer can each be independently in the range of 55 to 95.

[0031] The base layer may include a polyolefin-based membrane.

[0032] The first electrolyte layer may contain a cured product of the first electrolyte composition, and the second electrolyte layer may contain a cured product of the second electrolyte composition.

[0033] Inorganic particles can be disposed in the first electrolyte layer and the second electrolyte layer.

[0034] The battery separator may further include a first inorganic layer disposed between the substrate layer and the first electrolyte layer; and a second inorganic layer disposed between the substrate layer and the second electrolyte layer, and inorganic particles may be disposed in the first inorganic layer and the second inorganic layer.

[0035] Inorganic particles may consist of lithium-ion conductive first inorganic particles and flame-retardant second inorganic particles.

[0036] The first inorganic particle may include Li x Ti y (PO4)3(0 <x<2,0<y<3)、Li x Al y Ti z (PO4)3(0 <x<2,0<y<1,0<z<3)、Li x La y TiO3 (0 <x<2,0<y<3)、Li 6+x La3Zr 2-y M y O 12-z (0≤x≤1, 0≤y≤0.5, 0≤z≤0.2), or combinations thereof.

[0037] The first inorganic particle can be a polygonal inorganic particle, and the average size (nm) of the first inorganic particle can be in the range of 100 to 500.

[0038] The second inorganic particle may include SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, Zn2SnO4, ZnSnO3, ZnSn(OH)6, ZrO2, Y2O3, Al2O3, AlOOH, Al(OH)3, TiO2, or combinations thereof.

[0039] The second inorganic particle can be a needle-shaped inorganic particle or a plate-shaped inorganic particle.

[0040] The second inorganic particle can be a needle-shaped inorganic particle, the average longitudinal length (nm) of the second inorganic particle can be in the range of 300 to 1000, and the average transverse length (nm) of the second inorganic particle can be in the range of 25 to 60.

[0041] The true density of the first inorganic particle can be less than the true density of the second inorganic particle, the green density of the first inorganic particle can be greater than the green density of the second inorganic particle, and the battery separator can contain the first inorganic particle at a weight greater than the weight of the second inorganic particle.

[0042] Another embodiment of the present invention is a battery comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, wherein the separator comprises a substrate layer; a first electrolyte layer disposed on one surface of the substrate layer and comprising a first electrolyte composition; a second electrolyte layer disposed on the other surface of the substrate layer and comprising a second electrolyte composition; and inorganic particles, wherein the solid content (by weight) of the first electrolyte composition is greater than the solid content (by weight) of the second electrolyte composition.

[0043] The negative electrode may contain lithium metal, a first electrolyte layer may be disposed adjacent to the negative electrode, and a second electrolyte layer may be disposed adjacent to the positive electrode.

[0044] Beneficial effects

[0045] One surface of the battery separator of the present invention can buffer external physical stimuli, and the other surface can increase ion conductivity.

[0046] Even when the negative electrode expands, the battery of the present invention can protect the positive electrode and at the same time exhibit excellent electrical performance. Detailed Implementation

[0047] This document may use ordinal numbers such as “first” and “second” to refer to multiple components. There is no order of precedence among the components.

[0048] In this document, when a specific commercial product is used as a component, the characteristics of that component may refer to the characteristics specified in the product's technical data sheet (TDS) or certificate of analysis (COA).

[0049] In this document, when the physical properties of a particular material vary with temperature and pressure, the physical properties can be measured at room temperature (25°C) and atmospheric pressure (101.325 kPa). This is based on SATP (Standard Ambient Temperature and Pressure) as defined in the CRC Handbook of Chemistry and Physics.

[0050] In this document, the numerical range "within the range of A to B" means "A or greater and B or less".

[0051] The values ​​mentioned in this document are rounded. For example, 1.5 is a number in the range of 1.45 to 1.54.

[0052] The invention is described in more detail below.

[0053] One embodiment of the present invention is a battery separator.

[0054] In this document, a battery may include any device that performs an electrochemical reaction.

[0055] A battery can refer to any type of primary battery, secondary battery, fuel cell, solar cell, or capacitor. A battery can specifically refer to a lithium-ion secondary battery. Lithium-ion secondary batteries can include lithium metal secondary batteries, lithium polymer secondary batteries, lithium-ion polymer secondary batteries, or lithium-ion secondary batteries.

[0056] A battery separator can be disposed between the electrodes in a battery. Specifically, a battery separator can be disposed between the positive and negative electrodes in a battery. The battery separator prevents physical contact (short circuit) between the positive and negative electrodes in the battery. Charge carriers (e.g., lithium ions) can move between the electrodes through the battery separator.

[0057] The battery separator of the present invention includes a base layer, a first electrolyte layer, a second electrolyte layer, and inorganic particles.

[0058] The substrate layer allows fluid to move from one surface of the substrate layer to another.

[0059] A first electrolyte layer is disposed on one surface of the substrate layer. A second electrolyte layer is disposed on another surface of the substrate layer facing the first surface. Specifically, the first electrolyte layer may be disposed on a first surface of the substrate layer, and the second electrolyte layer may be disposed on a second surface of the substrate layer facing the first surface. The composition and thickness of the first electrolyte layer and the second electrolyte layer may be the same as or different from each other.

[0060] The first and second electrolyte layers can provide pathways through which charge carriers can move within the battery separator.

[0061] Inorganic particles can impart predetermined properties to battery separators. For example, inorganic particles can impart lithium-ion conductivity and / or thermal properties (heat resistance, flame retardancy, etc.) to battery separators.

[0062] The electrolyte layer contains an electrolyte composition. The composition contained in the first electrolyte layer is a first electrolyte composition. The composition contained in the second electrolyte layer is a second electrolyte composition. The electrolyte composition may be a gel polymer electrolyte composition.

[0063] In this document, the gel polymer electrolyte is a gel-phase electrolyte and comprises a polymer matrix and a liquid electrolyte impregnated within the polymer matrix. Here, the polymer matrix physically supports the gel polymer electrolyte. The liquid electrolyte imparts ionic conductivity to the gel polymer electrolyte.

[0064] In this document, an electrolyte composition refers to a composition that can become an electrolyte by itself or by a predetermined reaction.

[0065] In this invention, the first electrolyte layer and the second electrolyte layer exhibit different physical properties. This allows the battery separator of this invention to balance the positive and negative electrodes, particularly in batteries where the positive and negative electrodes exhibit different properties.

[0066] Specifically, the first electrolyte layer can exhibit properties that are harder than the second electrolyte layer. The second electrolyte layer can exhibit properties that are softer than the first electrolyte layer.

[0067] Conversely, the rigidity of the electrolyte layer can exhibit an inverse relationship with its ionic conductivity. That is, the ionic conductivity of the first electrolyte layer can be lower than that of the second electrolyte layer, and the ionic conductivity of the second electrolyte layer can be higher than that of the first electrolyte layer.

[0068] Unbound by theoretical constraints, it is believed that this is because the second electrolyte layer contains a larger amount of liquid electrolyte than the first electrolyte layer. Furthermore, it is also believed that this is because the contact between the second electrolyte layer and the adjacent electrode is superior to that between the first electrolyte layer and the adjacent electrode.

[0069] The rigidity and ionic conductivity of the electrolyte layer can vary depending on the solid content of the electrolyte composition contained in each layer. Electrolyte compositions with higher solid content can form a harder electrolyte layer, while electrolyte compositions with lower solid content can further improve the ionic conductivity of the electrolyte layer.

[0070] Therefore, the solid content (by weight) of the first electrolyte composition is greater than that of the second electrolyte composition (by weight).

[0071] Therefore, in which two electrolyte layers with opposite properties are arranged to face each other across the substrate, one surface of the battery separator of the present invention can buffer external physical stimuli, and the other surface can increase the ionic conductivity of the battery. Thus, the battery separator of the present invention is particularly suitable for batteries in which the positive and negative electrodes require opposite characteristics.

[0072] For example, the negative electrode of a lithium metal battery containing lithium metal as the negative electrode may expand during charging and discharging, causing cracks in the positive electrode. Here, the first electrolyte layer of the battery separator of the present invention can be disposed on the negative electrode side, while the second electrolyte layer can be disposed on the positive electrode side. The expansion of the negative electrode in the first electrolyte layer can be suppressed, and even if the negative electrode expands, the resulting problems can be mitigated by the buffering properties of the first electrolyte layer. Furthermore, since the second electrolyte layer is disposed adjacent to the positive electrode and can further improve ion conductivity, the decrease in ion conductivity caused by cracks in the positive electrode due to the expansion of the negative electrode can be reduced.

[0073] The solids content of an electrolyte composition can be defined as the ratio of the total weight of the components other than the liquid electrolyte to the weight of the composition. Specifically, the solids content of an electrolyte composition can be obtained by dividing the weight of the dried product of the electrolyte composition by its weight before drying and converting that value as a percentage (%). Methods for measuring the solids content of electrolyte compositions are discussed in more detail in the Examples section of this document.

[0074] The solid content of an electrolyte composition can be determined by factors such as the content of liquid electrolyte contained in the electrolyte composition and the number of crosslinks that may occur in the electrolyte layer. That is, when a crosslinking agent with a large number of functional groups participating in the crosslinking reaction of binder-crosslinking agent or crosslinking agent-crosslinking agent is used in a larger quantity, or when the crosslinking agent content of the electrolyte composition is high, the solid content of the electrolyte composition can be high.

[0075] The battery separator of the present invention is described in more detail below.

[0076] The solid content (SC1, wt%) of the first electrolyte composition can be in the range of 30 to 60. Preferably, the solid content (SC1, wt%) of the first electrolyte composition can be 35 or greater, 37.4 or greater, 38.4 or greater, 38.6 or greater, 40 or greater, or 41.2 or greater. The solid content (SC1, wt%) of the first electrolyte composition can be 55 or less, 50 or less, 45 or less, or 42 or less.

[0077] The solid content (SC2, wt%) of the second electrolyte composition can be in the range of 10 to 50. Preferably, the solid content (SC2, wt%) of the second electrolyte composition can be 15 or more, 20 or more, 24.2 or more, 25 or more, 27.5 or more, 28.1 or more, or 30 or more. The solid content (SC2, wt%) of the second electrolyte composition can be 45 or less, 40 or less, 35 or less, or 31 or less.

[0078] Whether the solid content of the first electrolyte composition is greater than the solid content of the second electrolyte composition can be determined by considering a margin of error. In this invention, even if the ratio (SC1 / SC2) of the solid content of the first electrolyte composition (SC1, wt%) to the solid content of the second electrolyte composition (SC2, wt%) is not exactly 1, if the ratio is less than 1.05, the solid content of the electrolyte composition and the solid content of the second electrolyte composition can be considered to be the same.

[0079] Therefore, the ratio (SC1 / SC2) of the solid content (SC1, wt%) of the first electrolyte composition to the solid content (SC2, wt%) of the second electrolyte composition can be 1.05 or greater.

[0080] Preferably, the ratio (SC1 / SC2) of the solid content (SC1, wt%) of the first electrolyte composition to the solid content (SC2, wt%) of the second electrolyte composition can be 1.1 or greater, 1.15 or greater, 1.20 or greater, 1.25 or greater, 1.30 or greater, 1.33 or greater, 1.35 or greater, 1.40 or greater, 1.45 or greater, 1.50 or greater, 1.55 or greater, 1.58 or greater, or 1.6. The ratio (SC1 / SC2) of the solid content (SC1, wt%) of the first electrolyte composition to the solid content (SC2, wt%) of the second electrolyte composition can be 5 or less, 4.5 or less, 4 or less, 3.5 or less, 3 or less, 2.5 or less, or 2 or less.

[0081] The electrolyte composition comprises a binder, a liquid electrolyte, and a crosslinking agent. A first electrolyte composition may comprise a first binder, a first liquid electrolyte, and a first crosslinking agent. A second electrolyte composition may comprise a second binder, a second liquid electrolyte, and a second crosslinking agent.

[0082] The binder can form a polymer matrix alone or together with a crosslinking agent.

[0083] Liquid electrolytes can be impregnated in a polymer matrix formed by a binder. Liquid electrolytes can impart ionic conductivity to gel polymer electrolytes.

[0084] Crosslinking agents, either alone or in combination with binders, can form a polymer matrix in a gel polymer electrolyte. Crosslinking agents can connect binders and / or crosslinking agents within the polymer matrix.

[0085] As described above, one method for designing a first electrolyte composition with a higher solids content than a second electrolyte composition is to provide a difference in liquid electrolyte content. Specifically, the first liquid electrolyte content (wt%) of the first electrolyte composition can be less than the second liquid electrolyte content (wt%) of the second electrolyte composition.

[0086] The liquid electrolyte content (by weight) of the first electrolyte layer can be in the range of 40 to 70%. Preferably, the liquid electrolyte content (by weight) of the first electrolyte layer can be 45 or greater, 50 or greater, 55 or greater, or 58.8 or greater. The liquid electrolyte content (by weight) of the first electrolyte layer can be 65 or less, 62.6 or less, 61.6 or less, 61.4 or less, or 60 or less.

[0087] The liquid electrolyte content (by weight) of the second electrolyte layer can be in the range of 50 to 90%. The liquid electrolyte content (by weight) of the second electrolyte layer can be 55 or greater, 60 or greater, 65 or greater, 69.1 or greater, 70 or greater, 71.9 or greater, or 72.5 or greater. The liquid electrolyte content (by weight) of the second electrolyte layer can be 85 or less, 80 or less, 75.8 or less, or 75 or less.

[0088] A binder can form a framework in the electrolyte layer formed from the electrolyte composition. The binder can have suitable crystallinity and polarity to enhance the ionic conductivity of the battery separator. Specifically, the polar portion of the binder can be bonded to a crosslinking agent. In this case, the binder can form a crosslinked structure in the electrolyte layer.

[0089] The first adhesive is an adhesive contained in the first electrolyte layer, and the second adhesive is an adhesive contained in the second electrolyte layer.

[0090] The first and second adhesives may each independently include fluorine-based adhesives. A fluorine-based adhesive can refer to an adhesive whose constituent units contain fluorine in whole or in part. Fluorine-based adhesives may include PVDF-based adhesives.

[0091] PVDF-based adhesives can be homopolymers or copolymers comprising polymeric units derived from vinylidene fluoride. Fluorine-based adhesives can comprise a first unit of vinylidene fluoride and a second unit of a fluorinated alkyl vinyl compound. That is, the first and second adhesives can each independently comprise a first unit of vinylidene fluoride and a second unit of a fluorinated alkyl vinyl compound. PVDF-based adhesives can be block copolymers or random copolymers comprising the first and second units. Preferably, PVDF-based adhesives can be random copolymers comprising the first and second units.

[0092] Fluorinated alkyl vinyl compounds can refer to those containing at least one C n H (2n+1-y) F y The indicated compound is a fluorinated alkyl group bonded to a vinyl group. However, it does not include vinylidene fluoride.

[0093] Fluorinated alkyl vinyl compounds may include at least one selected from vinyl fluoride, trifluoroethylene, tetrafluoroethylene, chlorotrifluoroethylene, and hexafluoropropylene. Preferably, the fluorinated alkyl vinyl compound may include at least one selected from hexafluoropropylene, tetrafluoroethylene, and chlorotrifluoroethylene. More preferably, the fluorinated alkyl vinyl compound may include hexafluoropropylene.

[0094] The content of the second unit in fluorine-based binders can be adjusted. The content of the second unit in fluorine-based binders may affect the crystallinity of fluorine-based binders, the ionic conductivity of the composite electrolyte, and the mechanical strength.

[0095] The content (by weight%) of the second unit of the first adhesive and the second adhesive can each independently range from 10 to 25. Preferably, the content (by weight%) of the second unit of the first adhesive and the second adhesive can each independently be 15 or greater, 16 or greater, 17 or greater, or 18 or greater. The content (by weight%) of the second unit of the first adhesive and the second adhesive can each independently be 23 or less, 21 or less, 20 or less, or 19 or less.

[0096] The content of the first and second units in each of the first and second adhesives can be determined by the fluorine-based adhesive. 19 F-NMR analysis was used for measurement.

[0097] The weight-average molecular weights of the first and second adhesives can also be adjusted. The weight-average molecular weights (g / mol) of the first and second adhesives can each independently range from 150,000 to 600,000. Preferably, the weight-average molecular weights (g / mol) of the first and second adhesives can each independently be 200,000 or greater, 250,000 or greater, 300,000 or greater, or 350,000 or greater. The weight-average molecular weights (g / mol) of the first and second adhesives can each independently be 550,000 or less, 500,000 or less, 450,000 or less, 400,000 or less, or 350,000 or less.

[0098] The weight-average molecular weights of the first and second binders can be measured by gel permeation chromatography.

[0099] The melting point of the fluorine-based adhesive can also be adjusted. The melting points (°C) of the first and second adhesives can each be independently in the range of 100 to 140. Preferably, the melting points (°C) of the first and second adhesives can each be independently 110 or higher, or 115 or higher. The melting points (°C) of the first and second adhesives can each be independently 135 or lower, 130 or lower, or 125 or lower.

[0100] The liquid electrolyte can be impregnated in a binder, specifically in a polymer matrix formed by the binder. The liquid electrolyte may also contain lithium salts and additives. The lithium salts can be dissolved in non-aqueous solvents.

[0101] Non-aqueous solvents can refer to organic solvents that do not contain water or contain only trace amounts of water. Non-aqueous solvents can include carbonate-based compounds, ether-based compounds, ester-based compounds, compounds containing polar functional groups, or mixtures thereof. Preferably, non-aqueous solvents can include carbonate-based compounds.

[0102] Ether-based compounds may include dimethoxyethane, diethoxyethane, tetrahydrofuran, or combinations thereof.

[0103] Ester-based compounds may include N-methyl-2-pyrrolidone (NMP), γ-butyrolactone (γ-butyrolactone), or combinations thereof.

[0104] Compounds containing polar functional groups may include dimethyl sulfoxide, acetonitrile, or combinations thereof.

[0105] Carbonate-based compounds may include linear carbonate-based compounds, cyclic carbonate-based compounds, or combinations thereof. Preferably, carbonate-based compounds may include both linear carbonate-based compounds and cyclic carbonate-based compounds.

[0106] In this invention, the electrolyte layer may contain a linear carbonate-based compound in a volume larger than the volume of the cyclic carbonate-based compound. Specifically, the electrolyte composition may contain a linear carbonate-based compound in a volume larger than the volume of the cyclic carbonate-based compound. The first electrolyte layer and the second electrolyte layer may each independently contain a linear carbonate-based compound in a volume larger than the volume of the cyclic carbonate-based compound. Specifically, the first electrolyte composition and the second electrolyte composition may each independently contain a linear carbonate-based compound in a volume larger than the volume of the cyclic carbonate-based compound. In this case, the miscibility of the binder with the liquid electrolyte is increased, and abnormal viscosity increases in the electrolyte composition can be prevented.

[0107] In this document, linear carbonate-based compounds refer to open-chain diesters of carbonic acid. Specifically, linear carbonate-based compounds include structures in which the two hydroxyl groups of carbonic acid are esterified with different alcohols and the entire molecule does not form a ring.

[0108] In this document, compounds based on cyclic carbonates refer to lactones whose ring structure includes a -O-CO-O- skeleton of a carbonate group. Specifically, compounds based on cyclic carbonates include structures in which two hydroxyl groups in a molecule form ester bonds with the same carbonate group at both ends, and the ring includes an -O-CO-O- skeleton.

[0109] Compounds based on linear carbonates may include dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl ethyl carbonate, or combinations thereof.

[0110] Specifically, linear carbonate-based compounds may include dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, or combinations thereof.

[0111] More specifically, linear carbonate-based compounds may include ethyl methyl carbonate.

[0112] Compounds based on linear carbonates can be liquids at room temperature.

[0113] Compounds based on cyclic carbonates may include ethylene carbonate, vinylene carbonate, ethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, propylene carbonate, butyl carbonate, or combinations thereof.

[0114] Specifically, compounds based on cyclic carbonates may include ethylene carbonate, vinylene carbonate, ethylene carbonate, fluoroethylene carbonate, propylene carbonate, butyl carbonate, or combinations thereof.

[0115] More specifically, compounds based on cyclic carbonates may include ethylene carbonate, vinylene carbonate, ethylene carbonate, propylene carbonate, or combinations thereof.

[0116] From the perspective of the miscibility of the binder and liquid electrolyte, the viscosity adjustment of the electrolyte composition, and the safety of the battery, it is preferable that the linear carbonate-based compound and the cyclic carbonate-based compound are combined in different phases.

[0117] Compounds based on cyclic carbonates can be solid at room temperature. Specifically, compounds based on cyclic carbonates may include ethylene carbonate.

[0118] The amounts of linear carbonate-based compounds and cyclic carbonate-based compounds used can also be appropriately adjusted within the range that the above conditions are met.

[0119] The volume (volume %) of the linear carbonate-based compound in the first electrolyte layer and the volume (volume %) of the linear carbonate-based compound in the second electrolyte layer can each be independently in the range of 55 to 95.

[0120] Preferably, the volume (volume %) of the linear carbonate-based compound in the first electrolyte layer and the volume (volume %) of the linear carbonate-based compound in the second electrolyte layer can each independently be 60 or greater, 65 or greater, or 70 or greater. The volume (volume %) of the linear carbonate-based compound in the first electrolyte layer and the volume (volume %) of the linear carbonate-based compound in the second electrolyte layer can each independently be 90 or less, 85 or less, 80 or less, or 75 or less.

[0121] The volume (volume %) of the cyclic carbonate-based compound in the first electrolyte layer and the volume (volume %) of the cyclic carbonate-based compound in the second electrolyte layer can each independently range from 5 to 45. Preferably, the volume (volume %) of the cyclic carbonate-based compound in the first electrolyte layer and the volume (volume %) of the cyclic carbonate-based compound in the second electrolyte layer can each independently be 10 or greater, 15 or greater, 20 or greater, or 25 or greater. The volume (volume %) of the cyclic carbonate-based compound in the first electrolyte layer and the volume (volume %) of the cyclic carbonate-based compound in the second electrolyte layer can each independently be 40 or less, 35 or less, or 30 or less.

[0122] The volume of linear carbonate-based compounds and cyclic carbonate-based compounds in the electrolyte layer can be adjusted by the volume of linear carbonate-based compounds and the volume of cyclic carbonate-based compounds in the electrolyte composition.

[0123] Lithium salts can refer to materials that decompose into lithium cations and anions upon dissociation.

[0124] Lithium salts may include LiPF6, LiBF4, LiCl, LiBr, LiI, LiClO4, LiAsF6, LiCH3CO2, LiCF3SO3, LiN(CF3SO2)2, LiN(FSO2)2, LiC(CF2SO2)3, or combinations thereof. Preferably, lithium salts may include LiPF6.

[0125] Additives can refer to substances that are applied in small amounts to liquid electrolytes to stabilize the electrode interface, improve electrochemical stability, regulate conduction characteristics, improve temperature characteristics, and inhibit gas generation.

[0126] The additive may include vinylene carbonate, 1,3-propanesulfonyl lactone, 1,3-propenesulfonyl lactone, lithium difluorophosphate, lithium tetrafluoro(oxalate)phosphate, lithium bis(fluorosulfonyl)imide, fluoroethylene carbonate, ethylene ethylene carbonate, or combinations thereof. Preferably, the additive may include vinylene carbonate.

[0127] Because the liquid electrolyte is impregnated in the binder or a polymer matrix formed from the binder in the electrolyte layer, the thickness of the electrolyte layer can typically be thick. Specifically, the electrolyte layer can be thicker than the substrate layer. More specifically, the first electrolyte layer and the second electrolyte layer can each be independently thicker than the substrate layer.

[0128] Crosslinking agents can include a plurality of types of crosslinking agents. Specifically, crosslinking agents include crosslinking agents with different numbers of crosslinkable functional groups. A first crosslinking agent may comprise a first-1 crosslinking agent and a first-2 crosslinking agent. A second crosslinking agent may comprise a second-1 crosslinking agent and a second-2 crosslinking agent. The number of crosslinkable functional groups in the first-1 crosslinking agent may be greater than the number of crosslinkable functional groups in the first-2 crosslinking agent. The number of crosslinkable functional groups in the second-1 crosslinking agent may be greater than the number of crosslinkable functional groups in the second-2 crosslinking agent.

[0129] In this document, the number of crosslinkable functional groups in a crosslinking agent (or compound) may refer to the number of crosslinkable functional groups per molecule of crosslinking agent (compound). Crosslinkable functional groups can be functional groups used to connect binders and / or crosslinking agents in a polymer matrix.

[0130] When an electrolyte composition contains multiple crosslinking agents with different numbers of crosslinkable functional groups, an electrolyte layer can be formed at a fast crosslinking rate, and the electrolyte layer can exhibit high crosslinking density and appropriate flexibility. This is believed to be because the first and second crosslinking agents can form a dense crosslinked structure, and the first and second crosslinking agents can provide spaces in which liquid electrolytes can be impregnated.

[0131] Crosslinking agents can each independently comprise a plurality of crosslinking agents distinguished by the molecular form of the central portion. Crosslinking agents can include monomeric compounds and polymeric compounds.

[0132] The first-1 crosslinking agent and the second-1 crosslinking agent may each independently comprise a monomer compound. The first-2 crosslinking agent and the second-2 crosslinking agent may each independently comprise a polymer compound.

[0133] Monomer compounds can refer to compounds whose remainder, excluding the crosslinkable functional groups, originates from monomers. Polymer compounds can refer to compounds whose remainder, excluding the crosslinkable functional groups, originates from polymers. When the crosslinking agent with a larger number of functional groups is a monomer and the crosslinking agent with a smaller number of functional groups is a polymer, the superior properties of the electrolyte layer, such as crosslinking rate, crosslinking density, and flexibility, can be more appropriately exhibited.

[0134] The solid content of an electrolyte composition can be determined by the number of crosslinks that may occur in the electrolyte composition. That is, when a larger amount of crosslinking agent with a larger number of functional groups involved in crosslinking is included, or when the total crosslinking agent content of the electrolyte composition is high, the solid content of the electrolyte composition can be high.

[0135] For example, the content of the first crosslinking agent in the first electrolyte composition may be greater than the content of the second crosslinking agent in the second electrolyte composition. This may mean that the total crosslinking agent content of the first electrolyte composition is greater than the total crosslinking agent content of the second electrolyte composition.

[0136] The number of crosslinkable functional groups in the first-1 crosslinking agent and the number of crosslinkable functional groups in the second-1 crosslinking agent can each independently be 3 or more. In this case, the first-1 crosslinking agent and the second-1 crosslinking agent can form a dense crosslinked structure. Specifically, the number of crosslinkable functional groups in the first-1 crosslinking agent and the number of crosslinkable functional groups in the second-1 crosslinking agent can each independently be 6 or less, 5 or less, or 4 or less.

[0137] The crosslinkable functional group may include a photoreactive functional group. Specifically, the crosslinkable functional group may include a (meth)acryloyl group as a photoreactive functional group. The crosslinking agent may include a multifunctional (meth)acrylate-based compound. Preferably, from the viewpoint of the rate of crosslinking reaction and preventing the electrochemical properties from deteriorating due to the rigidity of the polymer network, the crosslinkable functional group may include an acryloyl group as a photoreactive functional group.

[0138] Therefore, the first-1 crosslinking agent and the second-1 crosslinking agent may each independently include compounds based on tri(meth)acrylate, compounds based on tetra(meth)acrylate, compounds based on penta(meth)acrylate, compounds based on hexa(meth)acrylate, or combinations thereof.

[0139] Specifically, the first-1 crosslinking agent and the second-1 crosslinking agent may each independently include a triacrylate-based compound, a tetraacrylate-based compound, a pentaacrylate-based compound, a hexaacrylate-based compound, or a combination thereof.

[0140] More specifically, the first-1 crosslinking agent and the second-1 crosslinking agent may each independently include a triacrylate-based compound, a tetraacrylate-based compound, or a combination thereof.

[0141] More specifically, the first-1 crosslinking agent and the second-1 crosslinking agent may each independently comprise a triacrylate-based compound.

[0142] The first-1 crosslinking agent and the second-1 crosslinking agent may each independently include trimethylolpropane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, glycerol tri(meth)acrylate, ethoxylated glycerol tri(meth)acrylate, propoxylated glycerol tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and pentaerythritol tetra(methyl) Acrylates, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, erythritol tetra(meth)acrylate, bis(trimethylolpropane) tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ethoxylated dipentaerythritol penta(meth)acrylate, sorbitol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, sorbitol hexa(meth)acrylate, or combinations thereof.

[0143] Specifically, the first-1 crosslinking agent and the second-1 crosslinking agent may each independently include trimethylolpropane triacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, glycerol triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, tri(2-hydroxyethyl) isocyanurate triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, propoxylated pentaerythritol tetraacrylate, erythritol tetraacrylate, bis(trimethylolpropane) tetraacrylate, dipentaerythritol pentaacrylate, ethoxylated dipentaerythritol pentaacrylate, sorbitol pentaacrylate, dipentaerythritol hexaacrylate, ethoxylated dipentaerythritol hexaacrylate, sorbitol hexaacrylate, or combinations thereof.

[0144] More specifically, the first-1 crosslinking agent and the second-1 crosslinking agent may each independently include trimethylolpropane triacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, glycerol triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, tri(2-hydroxyethyl) isocyanurate triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, propoxylated pentaerythritol tetraacrylate, erythritol tetraacrylate, bis(trimethylolpropane tetraacrylate), or combinations thereof.

[0145] More specifically, the first-1 crosslinking agent and the second-1 crosslinking agent may each independently include trimethylolpropane triacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, glycerol triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, tri(2-hydroxyethyl)isocyanurate triacrylate, or combinations thereof.

[0146] The number of crosslinkable functional groups in the first-2 crosslinking agent and the number of crosslinkable functional groups in the second-2 crosslinking agent can each be independently less than the number of crosslinkable functional groups in the first-1 crosslinking agent and the number of crosslinkable functional groups in the second-1 crosslinking agent. If the number of crosslinkable functional groups in the first-1 crosslinking agent and the number of crosslinkable functional groups in the second-1 crosslinking agent are each independently 3, then the number of crosslinkable functional groups in the first-2 crosslinking agent and the number of crosslinkable functional groups in the second-2 crosslinking agent can each be independently 2. If the number of crosslinkable functional groups in the first-1 crosslinking agent and the number of crosslinkable functional groups in the second-1 crosslinking agent are each independently 4, then the number of crosslinkable functional groups in the first-2 crosslinking agent and the number of crosslinkable functional groups in the second-2 crosslinking agent can each be independently 2 or 3. If the number of crosslinkable functional groups in the first-1 crosslinking agent and the second-1 crosslinking agent are each independently 5, then the number of crosslinkable functional groups in the first-2 crosslinking agent and the second-2 crosslinking agent can each independently be 2, 3, or 4. If the number of crosslinkable functional groups in the first-1 crosslinking agent and the second-1 crosslinking agent are each independently 6, then the number of crosslinkable functional groups in the first-2 crosslinking agent and the second-2 crosslinking agent can each independently be 2, 3, 4, or 5.

[0147] Specifically, regardless of the number of crosslinkable functional groups in the first-1 crosslinking agent and the second-1 crosslinking agent, the number of crosslinkable functional groups in the first-2 crosslinking agent and the second-2 crosslinking agent can each be independently 2. When the number of crosslinkable functional groups in the first-2 crosslinking agent and the second-2 crosslinking agent is as small as possible, the crosslinking agent with a smaller number of crosslinkable functional groups can more smoothly provide the space in which a liquid electrolyte can be impregnated.

[0148] Since the crosslinking agent can contain photoreactive functional groups, specifically (meth)acryloyl groups, and the number of crosslinkable functional groups in the first-2 crosslinking agent and the second-2 crosslinking agent can be 2, the first-2 crosslinking agent and the second-2 crosslinking agent can each independently comprise compounds based on di(meth)acrylate.

[0149] Furthermore, since the photoreactive functional group preferably includes an acryloyl group, the first-2 crosslinker and the second-2 crosslinker can each independently comprise a diacrylate-based compound.

[0150] The first-2 crosslinking agent and the second-2 crosslinking agent may each independently include polyethylene glycol di(meth)acrylate, poly(ethylene oxide-propylene oxide) di(meth)acrylate, polyurethane di(meth)acrylate, polycarbonate di(meth)acrylate, or combinations thereof.

[0151] Specifically, the first-2 crosslinking agent and the second-2 crosslinking agent may each independently include polyethylene glycol diacrylate, poly(ethylene oxide-propylene oxide) diacrylate, polyurethane diacrylate, polycarbonate diacrylate, or a combination thereof.

[0152] More specifically, the first-2 crosslinking agent and the second-2 crosslinking agent may each independently comprise polyethylene glycol diacrylate, polyurethane diacrylate, or a combination thereof.

[0153] More specifically, the first-2 crosslinker and the second-2 crosslinker may each independently comprise polyurethane diacrylate.

[0154] When the first and second crosslinking agents each independently comprise a polymer compound, the molecular weight of the polymer compound can also be adjusted. The first and second crosslinking agents can each independently comprise polyethylene glycol diacrylate with a molecular weight in the range of 400 g / mol to 700 g / mol, polyurethane diacrylate with a molecular weight in the range of 1400 g / mol to 2100 g / mol, or a combination thereof. Specifically, the first and second crosslinking agents can each independently comprise polyurethane diacrylate with a molecular weight in the range of 1400 g / mol to 2100 g / mol.

[0155] The blending ratio of monomeric compounds to polymeric compounds can also be adjusted appropriately.

[0156] The weight ratio (C1-1:C1-2) of the first-1 crosslinking agent of the first electrolyte layer to the weight (C1-2) of the first-2 crosslinking agent of the first electrolyte layer, and the weight ratio (C2-1:C2-2) of the second-1 crosslinking agent of the second electrolyte layer to the weight (C2-2) of the second-2 crosslinking agent of the second electrolyte layer, can each be independently within the range of 1:9 to 9:1.

[0157] Preferably, the weight ratio (C1-1:C1-2) of the first-1 crosslinking agent of the first electrolyte layer to the weight ratio (C1-2) of the first-2 crosslinking agent of the first electrolyte layer, and the weight ratio (C2-1:C2-2) of the second-1 crosslinking agent of the second electrolyte layer to the weight ratio (C2-2) of the second-2 crosslinking agent of the second electrolyte layer can each independently be 1.5:8.5 or greater, 2:8 or greater, 2.5:7:5 or greater, 3:7 or greater, 3.5:6.5 or greater, 4:6 or greater, or 4.5:5.5 or greater. The weight ratio (C1-1:C1-2) of the first-1 crosslinking agent of the first electrolyte layer to the weight (C1-2) of the first-2 crosslinking agent of the first electrolyte layer, and the weight ratio (C2-1:C2-2) of the second-1 crosslinking agent of the second electrolyte layer to the weight (C2-2) of the second-2 crosslinking agent of the second electrolyte layer, can each independently be 8.5:1.5 or less, 8:2 or less, 7.5:2.5 or less, 7:3 or less, 6.5:3.5 or less, 6:4 or less, or 5.5:4.5 or less.

[0158] The weight ratio of the first crosslinking agent to the second crosslinking agent in the electrolyte layer can be adjusted by the content of the first crosslinking agent and the second crosslinking agent in each electrolyte composition.

[0159] The electrolyte composition may also contain an initiator. That is, the first electrolyte composition may also contain a first initiator. The second electrolyte composition may also contain a second initiator.

[0160] When a predetermined stimulus is applied, the initiator can initiate a reaction in which the binder forms a polymer matrix.

[0161] The first initiator and the second initiator may each independently include a thermal polymerization initiator, a photopolymerization initiator, or a combination thereof. Preferably, the first initiator and the second initiator may each independently include a photopolymerization initiator.

[0162] The first initiator and the second initiator may each independently include a short-wavelength photopolymerization initiator, a long-wavelength photopolymerization initiator, or a combination thereof. Preferably, the photopolymerization initiator may include a long-wavelength photopolymerization initiator.

[0163] Short-wavelength photopolymerization initiators may include IRGACURE 127 (1,1'-(methylene-di-4,1-phenylene)bis[2-hydroxy-2-methyl-1-propanone]), IRGACURE 1173 (2-hydroxy-2-methylphenylacetone, HMPP), DMPA (2,2-dimethoxy-2-phenylacetophenone), HOMPP (2-hydroxy-2-methylphenylacetone), LAP (phenyl-2,4,6-trimethylbenzoylphosphine), or combinations thereof.

[0164] Long-wavelength photopolymerization initiators may include at least one selected from bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide and ethyl (2,4,6-trimethylbenzoyl)phenylphosphine oxide. Preferably, the long-wavelength photopolymerization initiator may include ethyl (2,4,6-trimethylbenzoyl)phenylphosphine oxide (TPO-L).

[0165] The substrate layer may include a polyolefin-based membrane. Specifically, the substrate layer may include a porous polyolefin-based membrane.

[0166] Here, a polyolefin-based porous membrane refers to a porous membrane that contains a polyolefin-based resin as its main component.

[0167] Polyolefin-based porous membranes may contain polyolefin-based resin in an amount of 50% or more, 90% or more, or 95% or more of the total material constituting the polyolefin-based porous membrane.

[0168] The weight-average molecular weight of the components contained in polyolefin-based resins can be 3 × 10⁻⁶. 5 Up to 15×10 6 When the weight-average molecular weight of the components contained in a polyolefin-based resin is 1,000,000 or greater, the strength of the separator, including a polyolefin porous membrane, can be improved.

[0169] Polyolefin-based resins may include thermoplastic resins. Thermoplastic resins may include homopolymers (e.g., polyethylene, polypropylene, polybutene) or copolymers (e.g., ethylene-propylene copolymers) formed by the polymerization of monomers (e.g., ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene).

[0170] Polyolefin-based porous membranes can be layers containing only one of these polyolefin-based resins, or layers containing two or more of these polyolefin-based resins. Polyethylene and high-molecular-weight polyethylene, with ethylene as the main backbone, can block the flow of excessive current (shutdown) at lower temperatures. Furthermore, polyolefin-based porous membranes can also contain components other than the polyolefin-based resin that do not impair the membrane's function.

[0171] An electrolyte layer can be formed by curing an electrolyte composition. The electrolyte layer may contain a cured product of the electrolyte composition. A first electrolyte layer may contain a cured product of a first electrolyte composition. A second electrolyte layer may contain a cured product of a second electrolyte composition.

[0172] The curing method may include, for example, thermal curing, photocuring, and thermal-photocuring. Preferably, the curing method is photocuring.

[0173] The cured product of a composition can refer to a product that undergoes a chemical process in which the composition becomes harder or hardens as the structure of the components contained in the composition changes due to chemical reactions between the components. Curing can be different from drying, which is a physical process in which a portion of the composition dries or hardens as some of the components contained in the composition (e.g., solvents such as water, volatile components) evaporate.

[0174] Inorganic particles can exist in battery separators in various forms.

[0175] Inorganic particles can be disposed within the electrolyte layer. That is, inorganic particles can be disposed within the first electrolyte layer and the second electrolyte layer. Specifically, the first electrolyte composition and the second electrolyte composition may also contain inorganic particles. When the first electrolyte composition is cured, the inorganic particles can be disposed within the first electrolyte layer. When the second electrolyte composition is cured, the inorganic particles can be disposed within the second electrolyte layer. In this case, the first electrolyte layer and the second electrolyte layer can be in direct contact with the substrate layer. There may not be separate layers between the first electrolyte layer and the substrate layer, or between the second electrolyte layer and the substrate layer.

[0176] Inorganic particles can exist as a layer in the battery separator, independent of the substrate layer, the first electrolyte layer, and the second electrolyte layer.

[0177] The battery separator may further include an inorganic layer disposed between the substrate layer and the electrolyte layer. Specifically, the battery separator may further include a first inorganic layer disposed between the substrate layer and the first electrolyte layer; and a second inorganic layer disposed between the substrate layer and the second electrolyte layer. Inorganic particles may be disposed in the first and second inorganic layers. In this case, the first electrolyte layer, the second electrolyte layer, the first electrolyte composition, or the second electrolyte composition may not contain inorganic particles.

[0178] The type of inorganic particles can vary depending on the properties imparted to the battery separator by the inorganic particles. Specifically, the inorganic particles can include a combination of various types of inorganic particles that can impart different properties to the battery separator. When the battery separator contains multiple types of inorganic particles, it can exhibit improved mechanical properties, thermal properties, and ionic conductivity.

[0179] Inorganic particles may comprise first inorganic particles and second inorganic particles. The first and second inorganic particles may differ in terms of endowed properties, particle size, shape, and density. Specifically, inorganic particles may include lithium-ion conductive first inorganic particles and flame-retardant second inorganic particles.

[0180] Lithium-ion conductive inorganic particles may contain lithium but exhibit the function of facilitating lithium-ion movement without storing lithium. Certain defects may exist within these particles. Charge carriers, such as lithium ions, can utilize these defects to move. Therefore, lithium-ion conductive inorganic particles can improve lithium-ion conductivity in batteries. Consequently, battery performance can also be improved.

[0181] The first inorganic particle may include Li x Ti y (PO4)3(0 <x<2,0<y<3)、Li x Al y Ti z (PO4)3(0 <x<2,0<y<1,0<z<3)、Li x La y TiO3 (0 <x<2,0<y<3)、Li 6+x La3Zr 2-y M y O 12-z (0≤x≤1, 0≤y≤0.5, 0≤z≤0.2), or combinations thereof. Preferably, the first inorganic particle may include Li. x Al y Ti z (PO4)3(0 <x<2,0<y<1,0<z<3)。

[0182] The first inorganic particle can be a polygonal inorganic particle.

[0183] In this document, a polygonal particle can refer to a particle whose outer contour is composed of multiple straight lines in the form of a polyhedron. When the maximum length, maximum width, and maximum thickness of the polygonal particle are L, W, and T, respectively, L / W and W / T can each be in the range of 1 to 3. There are no particular restrictions on the shape of the polyhedron constituting the polygonal particle. A polygonal particle can be a particle with a polyhedral shape that satisfies the conditions of L, W, and T described above.

[0184] The average size (nm) of the first inorganic particle can be in the range of 100 to 500. Preferably, the average size (nm) of the first inorganic particle can be 150 or greater, 200 or greater, 250 or greater, 300 or greater, 310 or greater, 320 or greater, 324 or greater, or 330 or greater. The average size (nm) of the first inorganic particle can be 450 or less, 400 or less, 350 or less, or 340 or less.

[0185] The average size of the first inorganic particles can refer to the average of the maximum lengths of all particles. The average size of the first inorganic particles can be measured using a known particle size analyzer. Alternatively, the average size of the first inorganic particles can be measured using electron micrographs of the particles. The average of the maximum lengths of the first inorganic particles determined in the electron micrograph, expressed as the number of inorganic particles, can be considered the average size of the first inorganic particles.

[0186] Flame-retardant inorganic particles can add flame-retardant properties to battery separators and prevent the battery's internal temperature from rising sharply.

[0187] The second inorganic particles may include SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, Zn2SnO4, ZnSnO3, ZnSn(OH)6, ZrO2, Y2O3, Al2O3, AlOOH, Al(OH)3, TiO2, or combinations thereof. Preferably, the second inorganic particles may include ZrO2, Y2O3, Al2O3, AlOOH, Al(OH)3, TiO2, or combinations thereof. More preferably, the second inorganic particles may include Al2O3, AlOOH, Al(OH)3, TiO2, or combinations thereof.

[0188] The second inorganic particle can be a polygonal inorganic particle, a needle-shaped inorganic particle, or a plate-shaped inorganic particle. Preferably, the second inorganic particle can be a needle-shaped inorganic particle or a plate-shaped inorganic particle.

[0189] In this document, needle-like particles can refer to particles that are very long relative to their thickness or width, in the form of thin, elongated needles or fibers. When the maximum length, maximum width, and maximum thickness of the needle-like particles are L, W, and T, respectively, L / W or L / T can be 3 or greater.

[0190] In this document, flaky particles can refer to particles that are flat and sheet-like in shape due to their very thin thickness compared to their length or width. When the maximum length, maximum width, and maximum thickness of the flaky particles are L, W, and T, respectively, L / T or W / T can be 3 or greater.

[0191] Preferably, the second inorganic particle is a needle-shaped particle, and the transverse length and longitudinal length of the second inorganic particle can be adjusted independently. The longitudinal length of the second inorganic particle can be longer than the transverse length of the second inorganic particle.

[0192] The average longitudinal length (nm) of the second inorganic particle can range from 300 to 1000. The average transverse length (nm) of the second inorganic particle can range from 25 to 60.

[0193] Preferably, the average longitudinal length (nm) of the second inorganic particle can be 350 or greater, 400 or greater, 450 or greater, 500 or greater, 550 or greater, 597 or greater, or 600 or greater. The average longitudinal length (nm) of the second inorganic particle can be 900 or less, 800 or less, 700 or less, 650 or less, or 600 or less.

[0194] Preferably, the average lateral length (nm) of the second inorganic particle can be 30 or greater, 35 or greater, 40 or greater, 45 or greater, or 49 or greater. The average lateral length (nm) of the second inorganic particle can be 55 or less, 51 or less, or 50 or less.

[0195] The longitudinal length of the second inorganic particle can refer to its maximum length. The transverse length of the second inorganic particle can refer to the longer dimension among the dimensions measured in the direction perpendicular to the longitudinal direction.

[0196] The average longitudinal length of the second inorganic particles can be measured using electron microscopy images of the second inorganic particles. The average of the maximum lengths of each second inorganic particle determined in the electron microscopy image, expressed as the number of inorganic particles, can be considered the average longitudinal length of the second inorganic particles. Furthermore, the average of the lengths of each second inorganic particle measured in the electron microscopy image in the direction perpendicular to the maximum length, expressed as the number of inorganic particles, can be considered the average transverse length of the second inorganic particles.

[0197] The true density of the first inorganic particle can be less than that of the second inorganic particle. Inorganic particles can improve the mechanical and thermal properties of the battery separator by imparting rigidity and heat resistance. When the battery separator contains multiple types of inorganic particles with different densities, the heavier particles can form a framework at the bottom, while the lighter particles can fill the upper part or the gaps formed by the heavier particles. During this process, a uniform porous structure can be formed inside the battery separator. The uniform porous structure can enhance the electrolyte solution impregnation and ionic conductivity of the battery separator.

[0198] In this document, a uniform pore structure can refer to a structure in which the average size, shape, density, etc., of the pores are almost constant regardless of the position of the layers, so that the path of material movement within them can remain constant. A uniform pore structure can also refer to a state in which the size and spatial distribution of the pores vary little throughout the entire battery separator including the pores, the pores are continuously connected to each other, and the pores are not located in a specific direction or position.

[0199] In this document, the true density of a particle can refer to the density calculated solely from the particle's own mass and volume, excluding internal voids. The true density of inorganic particles can be a known value for the corresponding inorganic particle or a value measured using known methods. The true density of inorganic particles can be determined based on the chemical composition of the corresponding inorganic particle.

[0200] The true density of the first inorganic particle (g / cm³) 3 The value can be in the range of 1 to 3. Preferably, the true density (g / cm³) of the first inorganic particle is... 3 The true density (g / cm³) of the first inorganic particle can be 1.3 or greater, 1.5 or greater, 2.0 or greater, or 2.3 or greater. 3 () can be 2.7 or smaller, 2.5 or smaller, or 2.4 or smaller.

[0201] The true density of the second inorganic particle (g / cm³) 3 The value can be in the range of 2 to 5. The true density (g / cm³) of the second inorganic particle... 3 The true density (g / cm³) of the second inorganic particle can be 2.3 or greater, 2.5 or greater, 2.7 or greater, or 3.0 or greater. 3 () can be 4.7 or smaller, 4.5 or smaller, 4.0 or smaller, 3.5 or smaller, or 3.1 or smaller.

[0202] The green density of the first inorganic particles can be greater than that of the second inorganic particles.

[0203] In this document, the green density (compact density) of particles can refer to the density of particles in a compacted state after being processed into a predetermined shape. Green density reflects not only the density of the particles themselves but also the density of the voids between the particles. The methods for measuring the green density of inorganic particles are described in detail in the embodiments.

[0204] That is, in the battery separator, heavier inorganic particles can be arranged less densely, while lighter inorganic particles can be arranged more densely. As a result, a structure can be formed in which the heavier inorganic particles fill the pores formed by the lighter inorganic particles. When uniformly distributed pores are formed in the battery separator, the amount of electrolyte solution impregnated in the battery separator can be increased. Consequently, the ionic conductivity of the battery separator can be increased.

[0205] The green density of the first inorganic particles (g / cm³) 3 The density of the first inorganic particles can be in the range of 1 to 3. Preferably, the green density (g / cm³) of the first inorganic particles is... 3 The density of the first inorganic particles (g / cm³) can be 1.1 or greater, 1.2 or greater, 1.3 or greater, or 1.4 or greater. 3 () can be 2.5 or smaller, 2.0 or smaller, 1.9 or smaller, 1.8 or smaller, 1.7 or smaller, 1.6 or smaller, or 1.5 or smaller.

[0206] The green density of the second inorganic particles (g / cm³) 3 The green density (g / cm³) of the second inorganic particles can be in the range of 1 to 3. Preferably, the green density (g / cm³) of the second inorganic particles is... 3 The green density of the second inorganic particles can be 1.05 or greater, 1.10 or greater, or 1.15 or greater. 3 () can be 2.5 or smaller, 2.0 or smaller, 1.5 or smaller, 1.4 or smaller, 1.3 or smaller, 1.2 or smaller, or 1.17 or smaller.

[0207] The ratio of the first inorganic particles to the second inorganic particles in the battery separator can be determined by considering the function of each particle. The battery separator can contain the first inorganic particles at a weight greater than the weight of the second inorganic particles.

[0208] The content of the second inorganic particles in the battery separator (based on the total amount of the first and second inorganic particles, by weight%) can be 5 or greater. The content of the second inorganic particles in the battery separator (based on the total amount of the first and second inorganic particles, by weight%) can be 10 or greater, 15 or greater, 20 or greater, 25 or greater, or 30 or greater. The content of the second inorganic particles in the battery separator (based on the total amount of the first and second inorganic particles, by weight%) can be 50 or less, 45 or less, 40 or less, 35 or less, or 30 or less.

[0209] The true density relationship between the first inorganic particle and the second inorganic particle can be determined by the chemical composition of the compounds constituting the first and second inorganic particles.

[0210] The green density relationship between the first inorganic particles and the second inorganic particles can be determined by the shape and size of each of the first and second inorganic particles. As mentioned above, the shape of the first inorganic particle can be different from the shape of the second inorganic particle.

[0211] Furthermore, the electrolyte composition can be impregnated in the pores of the substrate layer. That is, the first electrolyte composition and the second electrolyte composition can be impregnated in the pores of the substrate layer. Therefore, at least a portion of the first electrolyte layer containing the cured product of the first electrolyte composition and / or at least a portion of the second electrolyte layer containing the cured product of the second electrolyte composition can be impregnated in the pores of the substrate layer.

[0212] UV curing can be used to form a first electrolyte layer and a second electrolyte layer on a substrate. UV curing is a method of forming cross-linked structures between binders, between binders and crosslinkers, or between crosslinkers using external force. According to the UV curing method, the process of binder forming the polymer matrix, the dispersion process of the binder and inorganic particles, and the impregnation process of the liquid electrolyte can be carried out in the same step.

[0213] The UV curing method may include the following steps. The numbering of the steps does not refer to their order:

[0214] (1) Preparation of a first electrolyte composition and a second electrolyte composition;

[0215] (2) Apply the first electrolyte composition to one surface of the substrate layer;

[0216] (3) Applying the second electrolyte composition to another surface of the substrate layer; and

[0217] (4) Irradiate the first electrolyte composition and the second electrolyte composition with UV light.

[0218] In step (1), the preparation of the electrolyte composition may include the direct preparation of the electrolyte composition or the application of a pre-prepared electrolyte composition.

[0219] There are no particular limitations on the application method and thickness conditions of the first electrolyte composition and the second electrolyte composition.

[0220] There are no particular restrictions on the conditions under which the first electrolyte composition and the second electrolyte composition are irradiated with UV light.

[0221] Another embodiment of the present invention is a battery.

[0222] A battery may include a first electrode, a second electrode, a separator, and an electrolyte. The separator may be disposed between the first electrode and the second electrode. The polarity of the first electrode may be opposite to that of the second electrode. If the first electrode is a positive electrode (negative electrode), then the second electrode may be a negative electrode (positive electrode).

[0223] The system consisting of a battery separator and an electrolyte can be the battery separator of the present invention. Therefore, in the description of the battery, the description of the separator and electrolyte can be completely replaced by the battery separator described above.

[0224] The positive electrode can be the electrode that undergoes a reduction reaction during discharge. The negative electrode can be the electrode that undergoes an oxidation reaction during discharge.

[0225] The electrodes of the battery may include electrode active materials attached to the electrode current collector. Specifically, the electrodes may include an electrode current collector and an electrode active material layer disposed on one or both surfaces of the electrode current collector and containing the electrode active material.

[0226] The positive electrode active material in the electrode active material may include a lithium intercalation material. The lithium intercalation material may include lithium transition metal oxides. The lithium intercalation material may include lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide and lithium iron oxide, lithium nickel manganese oxide, lithium nickel cobalt oxide, lithium nickel manganese cobalt oxide, or combinations thereof. Preferably, the positive electrode active material may include lithium nickel manganese cobalt oxide.

[0227] The negative electrode active material in the electrode active material may include a lithium intercalation material. The lithium intercalation material may include lithium-based metals, including lithium metal and lithium alloys; carbon-based compounds, including carbon, petroleum coke, activated carbon, and graphite; or combinations thereof.

[0228] The positive current collector can be a foil of a metal including aluminum, nickel, or a combination thereof. Preferably, the positive current collector can be an aluminum foil.

[0229] The negative electrode current collector can be a foil containing metals including copper, gold, nickel, or combinations thereof. Preferably, the negative electrode current collector can be a copper foil.

[0230] When the battery is a lithium metal battery, the battery separator of the present invention is more suitable. That is, the negative electrode can contain lithium metal. Specifically, the negative electrode can contain copper as the negative electrode current collector and can contain lithium metal as the negative electrode active material. In particular, the negative electrode can contain lithium metal as a major component (e.g., 90% by weight or more) as the negative electrode active material.

[0231] When the battery is a lithium metal battery, the first electrolyte layer can be disposed between the substrate layer and the negative electrode. Specifically, the first electrolyte layer can be disposed adjacent to the negative electrode. The second electrolyte layer can be disposed between the substrate layer and the positive electrode. Specifically, the second electrolyte layer can be disposed adjacent to the positive electrode.

[0232] Therefore, problems caused by negative electrode expansion during the charging and discharging of lithium metal batteries can be reduced, and battery performance can be improved.

[0233] Invention Embodiments

[0234] In the following document, the invention is described in more detail by way of examples and comparative examples. However, the invention is not limited to the examples.

[0235] [preparation]

[0236] Example 1. Battery separator

[0237] The battery separator is prepared according to the following steps.

[0238] (1) A dispersion was prepared by dispersing a mixture of 7 g of the first inorganic particles and 3 g of the second inorganic particles in 20 g of water. The first inorganic particles were LATP (polygonal Li-type polymer) from Ganfeng Lithium. 1.3 Al 0.3 Ti 1.7 P3O 12 True density: 2.3 g / cm³ 3 Green body density: 1.42 g / cm³ 3 Average size: 324 nm). The second inorganic particle is NNB (acicular boehmite) from Aramis; true density: 3.03 g / cm³. 3 Green body density: 1.15 g / cm³ 3 Average longitudinal length: 597 nm; Average longitudinal length: 49 nm.

[0239] (2) Add 0.1 g of thickener and 1 g of dispersant to the dispersion and stir with a homogenizer to prepare a slurry. The thickener is CMC2020 (carboxymethyl cellulose; degree of substitution: 1.00; viscosity: 15 mPa·s) from WEALTHY. The dispersant is CSB-400 (acrylic copolymer; glass transition temperature: -25℃; viscosity: 30 cP; solids content: 40 wt%) from Toyochem.

[0240] (3) The slurry was applied to the upper and lower surfaces of the substrate using a double-slit die and dried to prepare a structure in which the inorganic layer is disposed on the two surfaces of the substrate with a total thickness of 10 μm. The substrate was Asahi Kasei ND408A (PE film; thickness: 8 μm; porosity: 38%).

[0241] (4) A solution was prepared by adding 5 g of binder, 8 g of monomer crosslinker and 2 g of polymer crosslinker to 85 g of liquid electrolyte, stirring the solution with a homogenizer, and then adding 0.02 g of photopolymerization initiator to the solution to prepare the first electrolyte composition. The binder was Kynar 2501-20 (polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP); weight average molecular weight: 350,000 g / mol; HFP substitution rate: 18.6 wt%) from Arkema. The first crosslinker was M300 (trimethylolpropane triacrylate) from Miwon Specialty Chemical. The second crosslinker was Miramer PU2100 (polyurethane diacrylate, weight average molecular weight: 1400) from Miwon Specialty Chemical. The photopolymerization initiator was Omnirad TPO-L ((2,4,6-trimethylbenzoyl)phenylphosphine ethyl ester) from IGM. The liquid electrolyte is a liquid electrolyte in which 1 M LiPF6 is dissolved in a non-aqueous solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 3:7, and 2% by weight of ethylene carbonate (VC) is added based on the total weight.

[0242] (5) A solution was prepared by adding 1.67 g of binder, 2.67 g of monomer crosslinker and 0.67 g of polymer crosslinker to 95 g of liquid electrolyte, stirring the solution with a homogenizer, and then adding 0.07 g of photopolymerization initiator to the solution to prepare a second electrolyte composition.

[0243] (6) The first electrolyte composition is applied to the upper surface of the structure on which the inorganic layer is disposed, the second electrolyte composition is applied to the lower surface, and the structure is cured by UV irradiation to prepare a battery separator with a total thickness of 50 μm.

[0244] Example 2. Battery separator

[0245] The battery separator was prepared by repeating the same steps as in Example 1, except that in (4), 6 g of monomer crosslinking agent and 4 g of polymer crosslinking agent were added to prepare the first electrolyte composition.

[0246] Example 3. Battery separator

[0247] The battery separator was prepared by repeating the same steps as in Example 1, except that in (5), 2 g of monomer crosslinking agent and 1.34 g of polymer crosslinking agent were added to prepare the second electrolyte composition.

[0248] Example 4. Battery separator

[0249] The battery separator was prepared by repeating the same steps as in Example 1, except that in (4), a first electrolyte composition was prepared by adding 5 g of binder, 12 g of monomer crosslinker and 3 g of polymer crosslinker to 80 g of liquid electrolyte, and in (5), a second electrolyte composition was prepared by adding 1.67 g of binder, 4.66 g of monomer crosslinker and 1.17 g of polymer crosslinker to 92.5 g of liquid electrolyte.

[0250] Comparative Example 1. Battery separator

[0251] The battery separator is prepared by repeating the same steps as in Example 1, except that step (5) is omitted, and in (6), the first electrolyte composition is applied to the upper and lower surfaces of the structure on which the inorganic layer is disposed.

[0252] Comparative Example 2. Battery separator

[0253] The battery separator is prepared by repeating the same steps as in Example 2, except that step (5) is omitted, and in (6), the first electrolyte composition is applied to the upper and lower surfaces of the structure on which the inorganic layer is disposed.

[0254] Comparative Example 3. Battery separator

[0255] The battery separator is prepared by repeating the same steps as in Example 1, except that step (4) is omitted, and in (6), a second electrolyte composition is applied to the upper and lower surfaces of the structure on which an inorganic layer is disposed.

[0256] Comparative Example 4. Battery separator

[0257] The battery separator is prepared by repeating the same steps as in Example 3, except that step (4) is omitted, and in (6), the second electrolyte composition is applied to the upper and lower surfaces of the structure on which the inorganic layer is disposed.

[0258] Comparative Example 5. Battery separator

[0259] The battery separator is prepared by repeating the same steps as in Example 4, except that step (5) is omitted, and in (6), the first electrolyte composition is applied to the upper and lower surfaces of the structure on which the inorganic layer is disposed.

[0260] Comparative Example 6. Battery separator

[0261] The battery separator is prepared by repeating the same steps as in Example 4, except that step (4) is omitted, and in (6), a second electrolyte composition is applied to the upper and lower surfaces of the structure on which an inorganic layer is disposed.

[0262] [Evaluate]

[0263] Experimental Example 1. Shape of Inorganic Particles

[0264] The shape and size of the inorganic particles used in the examples and comparative examples were determined using SEM images. SEM images were taken according to the following steps.

[0265] (1) A dispersion of inorganic particles in ethanol was prepared by ultrasonic treatment (using UCP-10 from Lab Companion, 300 W, 40 kHz, 10 min, 25 °C) to disperse 5% by weight of the particles.

[0266] (2) Apply 1 mL of dispersion to the basement membrane (36 μm PET) with a dropper and dry it in a convection oven (without nitrogen or vacuum treatment, 80°C, 10 minutes).

[0267] (3) The dried membrane was attached to the sample stage of the SEM apparatus (FESEM-JSM7610F-plus, JEOL Inc.) via carbon tape (T01-215-015 from NISSHIN EM Co., Ltd.).

[0268] (4) Take images using a SEM device (accelerating voltage: 5 kV, working distance: 8.3 mm to 8.5 mm, SEM mode, magnification: 30,000 or 50,000).

[0269] (5) Use IMAGE J software to determine the shape of the inorganic particles identified in the obtained SEM images in the following manner. Select 50 inorganic particles for each SEM image.

[0270] 1) Needle-like particles: When the maximum length, maximum width, and maximum thickness are L, W, and T respectively, L / W or L / T is 3 or greater.

[0271] 2) Flaky particles: When the maximum length, maximum width, and maximum thickness of the particles are L, W, and T respectively, L / T or W / T is 3 or greater.

[0272] 3) Polygonal particles: When the maximum length, maximum width, and maximum thickness are L, W, and T respectively, L / W and W / T are each in the range of 1 to 3.

[0273] (6) The size of the inorganic particles identified in the obtained SEM images was measured using IMAGE J software in the following manner. Fifty inorganic particles were selected for each SEM image.

[0274] 1) Needle-shaped or flaky particles: The average longitudinal length is determined as the average of the maximum length of each inorganic particle based on the number of inorganic particles. The average transverse length is determined as the average of the length of each inorganic particle in the direction perpendicular to the maximum length based on the number of inorganic particles.

[0275] 2) Polygonal particles: The average size is determined as the average of the maximum length of each inorganic particle based on the number of inorganic particles.

[0276] Experimental Example 2. Green density of inorganic particles

[0277] The green density of inorganic particles is measured according to the following steps.

[0278] (1) The inorganic particles were pretreated by vacuum drying (80°C, 6 hours) followed by aging (25°C, 7 days).

[0279] (2) Place 1 g of pretreated inorganic particles into a cylindrical mold with a diameter of 16 mm.

[0280] (3) Subsequently, apply 1 ton / cm² to the cylindrical mold under the following conditions. 2 The pressure is used to prepare samples in the form of green discs.

[0281] Pressure application equipment: CARVER Inc. hydraulic press 4386,

[0282] Load application duration: 30 seconds

[0283] Suppression count: 1

[0284] (4) Measure the thickness of the center of the sample three times using a Mitutoyo CD-15APX and measure the volume of the sample by averaging the values.

[0285] (5) Calculate the green density of inorganic particles using the volume of the sample and the weight of the sample (1 g) measured in (4) above.

[0286] Experimental Example 3. Resistance and Ionic Conductivity

[0287] The following steps are used to evaluate the resistance and ionic conductivity of the battery separator.

[0288] (1) A coin cell with the battery separator positioned between SUS plates, as in the embodiments and comparative examples, was manufactured. The coin cell was a 2016 type, and the area of ​​the battery separator was 2.83 cm². 2 (19 pi).

[0289] (2) The resistance and ionic conductivity of the coin cell were calculated by applying resistance measurements using electrochemical impedance spectroscopy (EIS) and converting them via the Nyquist plot method. Resistance measurements were performed at AC voltage with an amplitude of 10 mV and a frequency of 1,000,000 Hz to 1,000 Hz.

[0290] Experimental Example 4. Gel content of the electrolyte composition

[0291] The gel content of the electrolyte composition is measured using the following steps.

[0292] (1) Measure the content (A) of the electrolyte composition sample.

[0293] (2) Dry the sample in a convection oven at 200°C for 24 hours.

[0294] (3) Measure the weight of the dried product (B).

[0295] (4) Perform the process of converting the weight ratio (B / A) of the electrolyte composition sample before (A) and after (B) drying into % three times, and determine the average value of the number of times as the gel content.

[0296] Experimental Example 5. Battery Performance

[0297] The following steps are used to measure the discharge capacity and capacity retention of batteries manufactured using battery separators.

[0298] (1) Preparation of such a slurry: wherein a mixture consisting of 94 wt% LiNiCoMnO2 (Ni:Co:Mn=8:1:1) as the positive electrode active material, 3 wt% conductive carbon black (Super P; IMERYS Graphite & Carbon) as the conductive material and 3 wt% polyvinylidene fluoride with a weight average molecular weight of about 800,000 as the binder is uniformly dispersed in NMP (N-methyl-2-pyrrolidone).

[0299] (2) The slurry was prepared at 4.0 mAh / cm 2 The loading amount is applied to a surface of a 20 μm thick aluminum current collector, followed by drying and rolling to prepare a positive electrode plate with a positive electrode active material layer on top.

[0300] (3) The positive electrode plate is stamped to 1.54 cm. 2 The size is (14 pi).

[0301] (4) Lithium metal (negative electrode active material layer) is rolled onto a 10 μm thick copper plate to manufacture a negative electrode plate with a total thickness of 100 μm.

[0302] (5) The negative electrode plate is stamped to 1.76 cm. 2 The size is (15 pi).

[0303] (6) Fabricating an electrode assembly having such a structure that the positive active material layer of the positive electrode plate and the negative active material layer of the negative electrode plate are arranged facing each other and are cut into 2.83 cm sections. 2 A battery separator of size (19 pi) is disposed between the positive electrode active material layer and the negative electrode active material layer.

[0304] (7) The electrode assembly is housed in a bag to complete the battery. Five battery samples are prepared. The performance of the battery is the arithmetic mean of the five samples.

[0305] Prepare the electrochemical analyzer (Toyo, Toscat-3100).

[0306] (8) Charge the battery in CC-CV mode at 0.2 C, 4.3 V and cut-off 0.05 C, and discharge the battery at 0.5 C, 3.0 V and cut-off 0.05 C.

[0307] (9) Measure the initial (first cycle) charging capacity and discharging capacity.

[0308] (10) Measure the charging capacity and discharging capacity after repeating 50 cycles.

[0309] [Results and Discussion]

[0310] Table 1 below shows the test results for the embodiments and comparative examples.

[0311] [Table 1]

[0312]

Claims

1. A battery separator, comprising: basal layer; A first electrolyte layer disposed on one surface of the substrate layer and comprising a first electrolyte composition; A second electrolyte layer disposed on another surface of the substrate layer and comprising a second electrolyte composition; and Inorganic particles, The solid content (by weight) of the first electrolyte composition is greater than the solid content (by weight) of the second electrolyte composition.

2. The battery separator according to claim 1, The ratio (SC1 / SC2) of the solid content (SC1, wt%) of the first electrolyte composition to the solid content (SC2, wt%) of the second electrolyte composition is 1.05 or greater.

3. The battery separator according to claim 1, The first electrolyte composition comprises a first binder, a first liquid electrolyte, and a first crosslinking agent. The second electrolyte composition comprises a second binder, a second liquid electrolyte, and a second crosslinking agent, and The content (by weight) of the first liquid electrolyte in the first electrolyte composition is less than the content (by weight) of the second liquid electrolyte in the second electrolyte composition.

4. The battery separator according to claim 3, The first adhesive and the second adhesive each independently comprise a first unit of vinylidene fluoride and a second unit of a fluorinated alkyl vinyl compound.

5. The battery separator according to claim 4, The weight-average molecular weight (g / mol) of the first adhesive and the second adhesive are each independently in the range of 150,000 to 600,000, and The content (by weight%) of the second unit of the first adhesive and the second adhesive is independently in the range of 10 to 25.

6. The battery separator according to claim 3, The first liquid electrolyte and the second liquid electrolyte each independently contain a non-aqueous solvent, a lithium salt, and an additive.

7. The battery separator according to claim 3, The first crosslinking agent comprises a first-1 crosslinking agent and a first-2 crosslinking agent. The second crosslinking agent comprises a second-1 crosslinking agent and a second-2 crosslinking agent. The number of crosslinkable functional groups in the first-1 crosslinking agent is greater than the number of crosslinkable functional groups in the first-2 crosslinking agent, and The number of crosslinkable functional groups in the second-1 crosslinking agent is greater than the number of crosslinkable functional groups in the second-2 crosslinking agent.

8. The battery separator according to claim 7, The first-1 crosslinking agent and the second-1 crosslinking agent each independently comprise monomeric compounds.

9. The battery separator according to claim 7, The number of crosslinkable functional groups in the first-1 crosslinking agent and the number of crosslinkable functional groups in the second-1 crosslinking agent are each independently 3 or greater.

10. The battery separator according to claim 7, The first-1 crosslinking agent and the second-1 crosslinking agent each independently include compounds based on tri(meth)acrylate, compounds based on tetra(meth)acrylate, compounds based on penta(meth)acrylate, compounds based on hexa(meth)acrylate, or combinations thereof.

11. The battery separator according to claim 7, The first-1 crosslinking agent and the second-1 crosslinking agent each independently include trimethylolpropane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, glycerol tri(meth)acrylate, ethoxylated glycerol tri(meth)acrylate, propoxylated glycerol tri(meth)acrylate, tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and pentaerythritol tetra(meth)acrylate. Pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, erythritol tetra(meth)acrylate, bis(trimethylolpropane) tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ethoxylated dipentaerythritol penta(meth)acrylate, sorbitol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, sorbitol hexa(meth)acrylate, or combinations thereof.

12. The battery separator according to claim 7, The first-2 crosslinking agent and the second-2 crosslinking agent each independently comprise a polymer compound.

13. The battery separator according to claim 7, The number of crosslinkable functional groups in the first-2 crosslinking agent and the number of crosslinkable functional groups in the second-2 crosslinking agent are both 2.

14. The battery separator according to claim 7, The first-2 crosslinking agent and the second-2 crosslinking agent each independently comprise a compound based on di(meth)acrylate.

15. The battery separator according to claim 7, The first-2 crosslinking agent and the second-2 crosslinking agent each independently include polyethylene glycol di(meth)acrylate, poly(ethylene oxide-propylene oxide) di(meth)acrylate, polyurethane di(meth)acrylate, polycarbonate di(meth)acrylate, or combinations thereof.

16. The battery separator according to claim 7, The weight ratio (C1-1:C1-2) of the first-1 crosslinking agent in the first electrolyte layer to the weight (C1-2) of the first-2 crosslinking agent in the first electrolyte layer, and the weight ratio (C2-1:C2-2) of the second-1 crosslinking agent in the second electrolyte layer to the weight (C2-2) of the second-2 crosslinking agent in the second electrolyte layer, are each independently within the range of 1:9 to 9:

1.

17. The battery separator according to claim 6, The first electrolyte layer and the second electrolyte layer each independently contain a linear carbonate-based compound in a volume larger than the volume of the cyclic carbonate-based compound.

18. The battery separator according to claim 17, The linear carbonate-based compounds mentioned above include dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl ethyl carbonate, or combinations thereof.

19. The battery separator according to claim 17, The linear carbonate-based compound is a liquid at room temperature.

20. The battery separator according to claim 17, The compounds based on cyclic carbonates include ethylene carbonate, vinylene carbonate, ethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, propylene carbonate, butyl carbonate, or combinations thereof.

21. The battery separator according to claim 17, The cyclic carbonate-based compound is a solid at room temperature.

22. The battery separator according to claim 17, The volume (volume %) of the linear carbonate-based compound in the first electrolyte layer and the volume (volume %) of the linear carbonate-based compound in the second electrolyte layer are each independently in the range of 55 to 95.

23. The battery separator according to claim 1, The base layer comprises a polyolefin-based membrane.

24. The battery separator according to claim 1, The first electrolyte layer comprises a cured product of the first electrolyte composition, and The second electrolyte layer comprises a cured product of the second electrolyte composition.

25. The battery separator according to claim 1, The inorganic particles are disposed in the first electrolyte layer and the second electrolyte layer.

26. The battery separator according to claim 1, further comprising: A first inorganic layer is disposed between the substrate layer and the first electrolyte layer; and A second inorganic layer is disposed between the substrate layer and the second electrolyte layer. The inorganic particles are disposed in the first inorganic layer and the second inorganic layer.

27. The battery separator according to claim 1, The inorganic particles comprise lithium-ion conductive first inorganic particles and flame-retardant second inorganic particles.

28. The battery separator according to claim 27, The first inorganic particle includes Li x Ti y (PO4)3(0 <x<2,0<y<3)、Li x Al y Ti z (PO4)3(0 <x<2,0<y<1,0<z<3)、Li x La y TiO3 (0 <x<2,0<y<3)、Li 6+x La3Zr 2-y M y O 12-z (0≤x≤1, 0≤y≤0.5, 0≤z≤0.2), or combinations thereof.

29. The battery separator according to claim 27, The first inorganic particle is a polygonal inorganic particle, and The average size (nm) of the first inorganic particle is in the range of 100 to 500.

30. The battery separator according to claim 27, The second inorganic particle includes SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, Zn2SnO4, ZnSnO3, ZnSn(OH)6, ZrO2, Y2O3, Al2O3, AlOOH, Al(OH)3, TiO2, or combinations thereof.

31. The battery separator according to claim 27, The second inorganic particle is either a needle-shaped inorganic particle or a plate-shaped inorganic particle.

32. The battery separator according to claim 27, The second inorganic particle is a needle-shaped inorganic particle. The average longitudinal length (nm) of the second inorganic particle is in the range of 300 to 1000, and The average transverse length (nm) of the second inorganic particle is in the range of 25 to 60.

33. The battery separator according to claim 27, The true density of the first inorganic particle is less than the true density of the second inorganic particle. The green density of the first inorganic particles is greater than the green density of the second inorganic particles, and The battery separator contains the first inorganic particles by a weight greater than the weight of the second inorganic particles.

34. A battery comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. The separator comprises a base layer; a first electrolyte layer disposed on one surface of the base layer and containing a first electrolyte composition; a second electrolyte layer disposed on the other surface of the base layer and containing a second electrolyte composition; and inorganic particles, and The solid content (by weight) of the first electrolyte composition is greater than the solid content (by weight) of the second electrolyte composition.

35. The battery according to claim 34, The negative electrode contains lithium metal. The first electrolyte layer is configured to be adjacent to the negative electrode, and The second electrolyte layer is configured to be adjacent to the positive electrode.